2008
DOI: 10.1289/ehp.10409
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Studies of Estrogen-Related Physical Findings in Infants

Abstract: BackgroundSoy formula containing estrogenic isoflavones is widely used in the United States. Infants consuming soy formula exclusively have high isoflavone exposures. We wanted to study whether soy formula prolonged the physiologic estrogenization of newborns, but available quantitative descriptions of the natural history of breast and genital development are inadequate for study design.ObjectiveWe piloted techniques for assessing infants’ responses to the withdrawal from maternal estrogen and gathered data on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 26 publications
1
52
0
2
Order By: Relevance
“…A recent cross-sectional study reported a higher prevalence of breast buds during the second year of life in female infants fed soy-based formula, when compared to their breast or cow-based formula fed counterparts (Zung et al, 2008). Similarly, a prospective study showed that human infants at times exhibited an estrogenized vaginal epithelium when fed soy-based formula as opposed to cowbased formula or breast-milk (Bernbaum et al, 2008). These data suggest that soy formula may prolong the physiologic estrogenization of the newborn.…”
Section: Soy-based Infant Formula: a Source For Concern?mentioning
confidence: 97%
“…A recent cross-sectional study reported a higher prevalence of breast buds during the second year of life in female infants fed soy-based formula, when compared to their breast or cow-based formula fed counterparts (Zung et al, 2008). Similarly, a prospective study showed that human infants at times exhibited an estrogenized vaginal epithelium when fed soy-based formula as opposed to cowbased formula or breast-milk (Bernbaum et al, 2008). These data suggest that soy formula may prolong the physiologic estrogenization of the newborn.…”
Section: Soy-based Infant Formula: a Source For Concern?mentioning
confidence: 97%
“…Initially developed as an alternative to bovine milk formulas for babies with a milk allergy, use of soy infant formula became more popular among environmentally oriented population with vegetarian life style. A recent prospective study in human infants observed that female infants fed soybased formulas exhibit estrogenized vaginal epithelium at times when their breast fed or cow milk-based formula fed peers did not (Bernbaum et al, 2008). Patisaul and Jefferson (2010) concluded that further determination if soy infant formula have long-term reproductive health effects should be a public health imperative.…”
Section: Effects On Female Reproductive Systemmentioning
confidence: 99%
“…Furthermore, another study showed that girls who consumed soy formula had a higher maturation index of vaginal cells compared to those fed breast or cow milk. 72 Collectively, both human and animal studies, thus far, support the hypothesis that early life exposures to dietary estrogens can induce effects on the reproductive tract; however, future longterm studies are needed to fully understand the impact of early soy isoflavone exposure. …”
Section: Effects On Indices Of Reproduction and Cancer Riskmentioning
confidence: 99%